Sustainable Circular Waste Management in the Urban Areas of Nepal - Subedi, Dol Raj (Academia Journal of Humanities & Social Sciences, 2026)
Pokhara Metropolitan City is experiencing a high degree of urbanization, making it a prime tourist destination in Nepal. As a consequence, more municipal solid wastes are being generated. Currently, the prevailing practices for managing these municipal wastes are mostly linear in nature, with minimal support from donors for recycling activities. Against this background, the relevance of governance structures and coordination in shaping the application of the principles of the circular economy within the context of managing wastes in Pokhara Metropolitan City was discussed in this study. A qualitative exploratory study design was applied for data collection. Interviews for collection of data were conducted with 12 influential informants. The study findings indicated that a lack of technical knowledge, poor application of policies, lack of clarity on institutional objectives, incoordination between donors and city administrators, and implications of decision-making for citizens regarding their activities for effective management of wastes, are factors that hampered the application of principles of the circular economy.